A Cu-Au bimetallic co-catalysis for the improved photocatalytic activity of TiO2 under visible light radiation. (October 2017) - Monga, Anila; Bathla, Aadil; Pal, Bonamali
Graphical abstract: This study disclose the sensitization and cocatalysis of the TiO2 by the core shell (Au@Cu) and reverse core shell (Cu@Au) bimetallic nanostructures compared to their monometallic counterparts for the effective photoxidation of salicylic acid and reduction of nitroaromatics under visible light irradiation. Highlights: Improved co-catalysis of Au@Cu and Cu@Au bimetallic nanostructures. High photocatalytic activity of Au@Cu/TiO2 and Cu@Au/TiO2 nanocatalysts. Visible light sensitivity of Au@Cu/TiO2 and Cu@Au/TiO2 nanocomposites. Superior photooxidation of salicylic acid and photoreduction of nitroaromatics. Abstract: This study represents the co-catalytic activity of mono/bimetallic loaded titanium dioxide (TiO2 ) nanocomposite of copper (Cu) & gold (Au) for the photo-reduction of aromatic nitro compounds and the photo-oxidation of salicylic acid. It was observed that the average hydrodynamic size of Cu (∼21 nm) and Au (∼25 nm) increased after the formation of core-shell structure (∼36 nm and∼38 nm for Cu@Au and Au@Cu respectively). The morphological studies revealed the uniform coating of Cu-shell of thickness∼2.1 nm over Au core. Moreover, in optical analysis a considerable blue-shift in the absorption band of Cu@Au (600 nm-559 nm) and a red-shift in Au@Cu (528–580 nm) with significant change in color were observed with increasing the amount of Au and Cu, respectively. Under visible light irradiation these bimetallic/TiO2 nanocomposite showed higher activity for the reduction of 3-nitroacetophenone and 1-chloro-3-nitrobenzene and oxidation of salicylic acid comparative to their monometallic counter parts with a higher rate constant k = 0.97 × 10 −2 min −1 (Au@Cu/TiO2 ), k = 0.65 × 10 −2 min −1 (Cu@Au/TiO2 ) relative to monometallic (k = 0.34 × 10 −2 min −1 (Cu/TiO2 ) and k = 0.29 × 10 −2 min −1 )) for the oxidation of salicylic acid. The higher activity of bimetallic/TiO2 nanocomposite is ascribed to the decrease in work function (4.2 for Au@Cu/TiO2 & 4.6 for Cu@Au/TiO2 ) resulting in the proficient transfer of electrons at bimetallic-TiO2 interface.